PENERAPAN MEDIA MULTIPLICATION STICK BOX DENGAN METODE JARIMAGIC UNTUK MENINGKATKAN KEAKTIFAN PADA MATA PELAJARAN MATEMATIKA - Puja, Puja Sukma Ismul Karomah (Prodi Pendidikan Guru Madrasah Ibtidaiyah STAIN Teungku Dirundeng Meulaboh, 2023)
Many students of SD Negeri 5 Ngembalrejo Kudus have difficulty in the material of multiplication calculation operations. Therefore, researchers apply teaching using a jarimatika method called jarimagic with learning media in the form of multiplication stick boxes. The goal is to determine the increase in the activeness of grade III students of SD Negeri 5 Ngembalrejo Kudus in mathematics subjects by applying the multiplication stick box media using the jarimagic method and overcoming learning difficulties experienced by grade III students of SD Negeri 5 Ngembalrejo . The method used in this research is quantitative which in data collection uses interviews, observations, and documentation as well as percentage results from cycles I and II. The results obtained from this study are that there is an increase in student learning activity. Cycle I in the results of observations of student learning activity obtained an average score of 62.72% categorized as quite active. while in the second cycle, the results of the student activity research obtained an average score of 75% categorized as students already quite active in the material of multiplication calculation operations. Keywords : finger method with stick box multiplication media, student activeness, multiplication calculation operation